Events Causing Happiness among Thai Factory Workers: A Case Study of Thai Toray Textile Mills Company - Chunin, Manop; Hean Foo, Koong; S. Adams, Austin (Kasetsart Journal of Social Sciences, 2015)
This qualitative research investigated the actual causes of happiness in the workplace via interviews. Eleven workers, of Thai Toray Textile Mills Company volunteered with permission of their supervisors, were key informants of this study. The results showed that four areas of events caused workers to feel happy: 1) events experienced with colleagues, good relationships with colleagues, being generous to colleagues, and creating humor at work; 2) events related to supervisors, concern for subordinates, and helping subordinates; 3) events related to the work environment; and 4) events related to subordinates, not exploiting others, optimism, attaining achievements, receiving more benefits than others, supporting others, participating in amusing activities, having good children, having good partnerships, concern for the family, having the chance to own a house, saving money for retirememt, earning money to pay for the higher education of their children, and taking a rest after retirement.